Randomised trial of parental support for families with very preterm children: outcome at 5 years. Issue 9 (17th May 2005) - Johnson, S; Ring, W; Anderson, P; Marlow, N
Abstract : Aims: To test the effectiveness of a home based developmental education intervention in improving outcome at 5 years for very preterm infants. Methods: The Avon Premature Infant Project (APIP) is a randomised controlled trial in which the parents of 284 babies born <33 weeks gestational age received a developmental education programme, a social support intervention, or standard care. A term reference population was also recruited. This study reports outcomes at 5 years (mean age 58 months 15 days) for 187 (66%) of these children without disability. Outcomes were assessed using the British Ability Scales II for cognitive development, the Movement ABC for motor impairment, and the Child Behavior Checklist for behavioural problems. Results: Preterm infants showed poorer cognitive performance than their term peers. Mean (SD) general conceptual ability (GCA) scores were: Portage 99.2 (15.7); parent adviser 100.3 (14.8); preterm control 101.1 (15.0); term reference 107.2 (13.4). There were no significant differences between preterm groups in GCA scores indicating no effect of either intervention. Similarly, there was no significant effect of intervention on behavioural or motor outcomes. Further analyses, in which outcome data were adjusted for social factors, did not reveal any differences between the three preterm groups or by subgroups classified by a range of perinatal variables. Conclusion: The small advantage shown at 2 years of age is no longer detectable at 5 years. These results question the effectiveness of early intervention in enhancing cognitive, behavioural, and motor function at 5 years.